2011
DOI: 10.4314/nvj.v31i2.68954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth performance and haematological response of broiler chicks to raw and boiled <i>Garcinia kola</i> seed diet

Abstract: SUMMARYThis study was set to evaluate the effect of raw and boiled (100 0 C) Garcinia kola seed diet on growth performance and haematological response of broiler chicks. A total 18 broiler chicks assigned into three treatment groups of six birds each were used for this study. Treatment one (control) received 0% inclusion of Garcinia kola seed. Treatment group two received 10% boiled Garcinia kola seed, while group three received 10% raw Garcinia kola seed in addition to basal feed (Vital starter and finisher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ebenebe et al [51] reported that as the dietary inclusion levels of G. kola increased from 2.5% to 7.5%, the weight gain of the rabbits was significantly depressed. Higher levels of GKSM had been previously reported to have growth-depressing effects on rabbits [31,52] and broiler birds [30]. The growth-depressing effects of higher GKSM may be due to the presence of tannins and oxalate.…”
Section: Growth Performance Indicesmentioning
confidence: 84%
See 2 more Smart Citations
“…Ebenebe et al [51] reported that as the dietary inclusion levels of G. kola increased from 2.5% to 7.5%, the weight gain of the rabbits was significantly depressed. Higher levels of GKSM had been previously reported to have growth-depressing effects on rabbits [31,52] and broiler birds [30]. The growth-depressing effects of higher GKSM may be due to the presence of tannins and oxalate.…”
Section: Growth Performance Indicesmentioning
confidence: 84%
“…These anti-nutrient factors (ANFs) reduce the bioavailability of minerals, such as calcium, which animals use. Higher tannins also bind to available proteins and make them either indigestible or unpalatable to animals [30], reducing the growth response. Interestingly, GKSM used in this study had a considerably low tannin content of 0.02% (Table -2).…”
Section: Growth Performance Indicesmentioning
confidence: 99%
See 1 more Smart Citation